A synthetic indicator of the quality of support for businesses in Burkina Faso, Cameroon, and Ghana - Jean C. Kouam; Simplice Asongu; Bin Joachem Meh; Robert Nantchouang; Fri L. Asanga; Denis Foretia (African Governance and Development Institute (AGDI), 2022)
This paper proposes a synthetic indicator of the quality of support for companies as well as identifies the factors that can contribute towards improving the quality of such support in three countries (i.e., Burkina-Faso, Cameroon, and Ghana). The approach used to construct this synthetic indicator builds on the works of Benzécri (1973) and Asselin (2002), who use static mechanics and apply techniques of factor analysis. A principal component analysis is performed on the data collected from 80 business support structures in the sampled countries. Afterconstructing the indicators, correlates are provided on how the constructed indicators are linked to the objectives of sustainable development. Our results are robust after controlling for variables relating to the general characteristics of the support structure. The findings are consistent with the thesis that taking sustainable development objectives into account in business support practices would significantly improve business performance in sampled countries and, by extension, in sub-Saharan Africa. The originality of the study stems from the fact that it considers specific SDGs (SDG4, SDG5, SDG8, and SDG9) and assesses their contribution to improving the quality of support for companies, a research area that has not been investigated hitherto by the extant literature. Implications for all stakeholders in the entrepreneurial ecosystem are discussed.
Keywords: C30; M20; O10; O30; O55; 330; Synthetic indicator; Quality of support; Businesses; Sub-Saharan Africa